The Way How Anthropological Culture Shapes Consumes: An Exploratory Comparative Study - Scaini, Luca (European Scientific Journal, ESJ, 2018)
The world today is discovering new forces clashing together and creating new threats and opportunities in terms of Globalization. Because these forces are mainly local, and not only economic, business today must take into consideration all different aspects, usually marginalized features, such as anthropology, traditions, and popular beliefs; weather and geography; religion and culture (Foegel, 1964 Parker, 19971, 2, 3, 2000, Scaini 2013, 20151,3, Weber 1904/05, 1906). These revitalizing and reinforcing instances are pushing/forcing “Globalization” to face new challenges, defined in the following: 1. Integration of different products with different cultures (Appiah, 2006), 2. adaptation of old products and retail marketing strategies to specific local needs based on physioeconomic factors (Pagania et al, 2015, Scaini 2012, 20151,3) and 3. How people in different environments buy the same products but consume them in different ways due to different cultural influences. The present paper intends to prove the original different consumes by comparing the cultural forces behind the consumption of the same goods in two different contexts: western and eastern markets. Moreover, the present exploratory study proofs different cultural motivations for consumers that pass through the unaffected bottleneck of purchase. Eventually, the anthropological instances that effectively and efficiently shape marketing strategies.